2018
DOI: 10.1136/thoraxjnl-2017-210593
|View full text |Cite
|
Sign up to set email alerts
|

NOTCH3 contributes to rhinovirus-induced goblet cell hyperplasia in COPD airway epithelial cells

Abstract: RV induces sustained GCH via NOTCH3 particularly in COPD cells or mice with COPD phenotype. This may be one of the mechanisms that may contribute to RV-induced prolonged airways obstruction in COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
63
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(71 citation statements)
references
References 42 publications
6
63
2
Order By: Relevance
“…191 Subsequent studies demonstrated that goblet cell gene expression was reduced following treatment with a gamma-secretase inhibitor (GSK L685,458) to limit NOTCH activation. 192 Further, supplementation of feed with quercetin reduced RVinduced lung inflammation (including neutrophilia), goblet cell metaplasia, and AHR. 193…”
Section: Mouse Asthma Exacerbation Modelsmentioning
confidence: 97%
“…191 Subsequent studies demonstrated that goblet cell gene expression was reduced following treatment with a gamma-secretase inhibitor (GSK L685,458) to limit NOTCH activation. 192 Further, supplementation of feed with quercetin reduced RVinduced lung inflammation (including neutrophilia), goblet cell metaplasia, and AHR. 193…”
Section: Mouse Asthma Exacerbation Modelsmentioning
confidence: 97%
“…inhibitor had no effect on RV-induction of MUC5AC and concluded that EGFR does not play a role in promoting virus-induced mucin expression in COPD 36 . However, in this study, the authors examined mucin expression solely at a late timepoint (15 days) post RV infection and did not evaluate effects of the treatment on mucin expression at earlier timepoints nor subsequent effects on production of inflammatory mediators.…”
Section: Et Al Recently Reported In Copd Airway Epithelial Cell Cultumentioning
confidence: 98%
“…Based on this knowledge, further studies are warranted to evaluate if cigarette smoke induced oxidative stress in the airway epithelium leads to impairment of lysosome-dependent NOTCH3 protein degradation.Despite the knowledge that NOTCH3 signaling plays an important role in regulating airway epithelial differentiation(12,14,17,32), the downstream signaling events and specific targets are largely unknown. Our demonstration that over-expression of NICD3 leads to increased expression of the goblet cell promoting transcription factor SPDEF(30) in HBECs, suggests that NOTCH3 regulates goblet cell differentiation at least in part via SPDEF-dependent mechanisms.…”
mentioning
confidence: 99%